Inovações sustentáveis na base da pirâmide: estudo de multicasos de empresas brasileiras - Bora, Sarita Monteiro (2010)
Due to environmental degradation, stemming mainly from increased consumption and industrial activities, since the 1960s, organizations are aiming for a narrowing between technological progress and the promotion of social and environmental well-being. With the growing concern for the environment, sustainable management has become a key differentiator and thus organizations seek, through innovation in products and services, meet the new market demands. However, efforts directed towards efficient environmental management are typically driven by the demands of established markets. Nevertheless, Hart and Christensen (2002) argue that emerging markets, also known as "base of the pyramid", represent great business opportunities, as they are considered ideal for welcome new environmentally friendly technologies and high impact. In this sense, the purpose of this dissertation was to analyze the sustainable innovations developed by Brazilian organizations to the base of the pyramid. Specifically, by characterizing the sustainable innovations aimed at the base of the pyramid developed by Brazilian organizations; identifying the determinants of sustainable innovations to the base of the pyramid markets; justifying the reasons for the adoption of sustainable innovations aimed at the base of the pyramid considering the perspective of the Institutional Theory. The analysis of data was through descriptive analysis of multiple case study, which is commonly suggested by authors to fill gaps in empirical contribution. Data analysis was carried out individually and cross-case. Based on the characterization found, the results show that at the national level, sustainable innovations developed for the bottom of the pyramid are still in an incipient moment, because although they provide small benefits under social and environmental point of view, they do not produce large impacts on society as a whole. It was also verified the existence of determinants that stimulated the development of these innovations in the cases studied such as regulations, incentives, base of pyramid market, specific firm factors and sustainable technology. These findings served to delineate the mechanisms of institutional isomorphism present in the analyzed cases. It was found that the coercive isomorphism is still very dominant, being the predominant reason for the adoption of sustainable innovations in the bottom of the pyramid, followed by mimetic isomorphism.